Modification of pool boiling regimes by sand deposition. Issue 2 (15th December 2019) - Mazor, Gedalia; Ladizhensky, Izhak; Shapiro, Alexander; Nemirovsky, Dimitry
Abstract: Sand spots, attached to a copper ball surface by means of polyvinyl acetate adhesive and distributed over the surface with areal density that ranges between one spot per 1.18 cm 2 (for low‐density spots) and one spot per 0.51 cm 2 (for high‐density spots), serve as a temporary heat transfer enhancer during the quenching in liquid nitrogen. Highest heat flux densities, achieved during quenching, lie in the range 10.8 to 20.2 W/cm 2, depending on the sand layer structure. Application of the temporary enhancer increases an amount of heat, evacuated by highly effective nucleate and transition boiling, by factor of 4.5 as compared with the bare sample. The process of sand layer preparation, data acquisition peculiarities, relationship between heat exchange efficiency and the spots areal density, along with sand grit size are discussed in this paper.